Sustainable food systems from agriculture to industry : improving production and processing - Galanakis, Charis M. (Academic Press, an imprint of Elsevier, 2018)
Sustainable Food Systems from Agriculture to Industry: Improving Production and Processing addresses the principle that food supply needs of the present must be met without compromising the ability of future generations to meet their needs. Responding to sustainability goals requires maximum utilization of all raw materials produced and integration of activities throughout all production-to-consumption stages. This book covers production stage activities to reduce postharvest losses and increase use of by-products streams (waste), food manufacturing and beyond, presenting insights to ensure energy, water and other resources are used efficiently and environmental impacts are minimized. The book presents the latest research and advancements in efficient, cost-effective, and environmentally friendly food production and ways they can be implemented within the food industry. Filling the knowledge gap between understanding and applying these advancements, this team of expert authors from around the globe offer both academic and industry perspectives and a real-world view of the challenges and potential solutions that exist for feeding the world in the future. The book will guide industry professionals and researchers in ways to improve the efficiency and sustainability of food systems.